Are There Upper Limits in Tumor Burden for Down‐Staging of Hepatocellular Carcinoma to Liver Transplant? Analysis of the All‐Comers Protocol. Issue 4 (12th April 2019) - Sinha, Jasmine; Mehta, Neil; Dodge, Jennifer L.; Poltavskiy, Eduard; Roberts, John; Yao, Francis
Abstract : Patients with hepatocellular carcinoma (HCC) within the University of California, San Francisco down‐staging (UCSF‐DS) criteria (one lesion > 5 cm and ≤ 8 cm; two to three lesions each ≤ 5 cm; or four to five lesions each ≤ 3 cm with total tumor diameter ≤ 8 cm) who achieved successful down‐staging (DS) to Milan criteria had similar outcomes after liver transplantation (LT) compared with HCC initially meeting the Milan criteria. Nevertheless, little is known about the outcome of DS in patients with initial tumor burden exceeding the UCSF‐DS criteria, defined as "all‐comers" (AC). We compared the intention‐to‐treat (ITT) outcomes of DS in 74 patients in the AC group and 133 patients in the UCSF‐DS group. Successful DS to Milan was observed in 64.8% of the AC group versus 84.2% of the UCSF‐DS group ( P < 0.001). The sum of tumor number and largest tumor diameter was significantly associated with successful DS (hazard ratio [HR] 0.87, P < 0.05). The cumulative probability of dropout within 1 year and 3 years was 53.5% and 80.0%, respectively, for AC versus 25.0% and 36.1%, respectively, for UCSF‐DS ( P < 0.0001). Factors predicting dropout included sum of tumor number and largest tumor diameter greater than 8 (HR 1.79, P = 0.049) and Child class B and C (HR 2.54, P = 0.001). The AC group also had a significantly lower liver transplant (LT) rate (13.5% versus 59.0%, P < 0.001). ITT survival at 1 year and 5 years was 77.4% and 21.1%, respectively, in AC versus 85.5% and 56.0%, respectively, in UCSF‐DS ( P < 0.001). Three of 10 patients in the AC group who underwent LT developed HCC recurrence. Conclusion: We observed a significantly lower LT probability and inferior ITT survival with DS in the AC group versus the UCSF‐DS group. Our results suggest that an upper limit in tumor burden exists beyond which successful LT after DS becomes an unrealistic goal.